THE EFFECT OF CLASSROOM MANAGEMENT AND WORK ETHIC ON EFFECTIVE LEARNING IN STATE SENIOR HIGH SCHOOLS IN NAMLEA DISTRICT - Aridila, Febri Rahmadani; T. Laurens , T. Laurens; A. Sahalessy , A. Sahalessy (Jurnal Konseling Pendidikan Islam, 2025)
This study aims to analyze the influence of classroom management and work ethic on effective learning among public high school teachers in Namlea District. The background of this study is based on the importance of teachers' role in creating a conducive learning environment and professionalism as the main factors in improving the quality of the teaching and learning process. This study uses a quantitative approach with an explanatory method and an ex post facto research design. The population of this study consists of all public high school teachers in Namlea District, and the sampling technique used was proportional random sampling. Data collection was conducted using a questionnaire with a Likert scale, which was then analyzed using multiple linear regression after undergoing validity, reliability, and classical assumption tests. The results of the study indicate that both classroom management and work ethic have a positive and significant impact on effective learning, with regression coefficients of 0.482 and 0.396, respectively, and significance levels of 0.000. The coefficient of determination (R²) of 67.2% indicates that the variables of classroom management and work ethic simultaneously explain most of the variation in learning effectiveness. These findings confirm that strengthening teachers' capacity to manage classrooms professionally and maintain a high work ethic is key to creating meaningful and quality learning, especially in areas with limited facilities and geographical challenges, such as the Namlea District. This study provides practical implications for the development of educational policies that emphasize continuous training in classroom management and work ethic development for teachers.